TINJAUAN MAQASHID AL-SYARI’AH TERHADAP PERILAKU SODOMI SEBAGAI ALASAN PERCERAIAN (Studi Putusan Nomor 222/Pdt.G/2019/PA.Bgr) - Alfin, Aidi; Bahar, Muchlis; Azwar, Zainal; Fathurohman, Muhammad Faozan (Tahkim (Jurnal Peradaban dan Hukum Islam), 2024)
Islam has taught married couples to get along well (mu'asyarah bil al-ma'ruf) including sexual relations. However, there are several cases of sexual deviation, including cases of sodomy. In the Bogor religious court, there was a case of sodomy as a reason for divorce. This research aims to analyze Maqashid al-Shariah's review of sodomy behavior as a reason for divorce. This type of research is normative qualitative using the statue appoarch or statutory approach and library study data collection techniques. The results of this research show that the judge's decision in decision number 222/Pdt.G/2019/PA.Bgr which granted the petition for divorce was in accordance with the concept of maqashid al-syari'ah because it had saved the wife from harm due to deviant behavior committed by her husband and the judge. assess that domestic happiness will not be realized if the marital relationship is maintained. In addition, sodomy behavior is contrary to the concept of maqashid al-syari'ah because it threatens the existence of religion (Hifzh al-Din), soul (Hifzh an-Nafs), and offspring (Hifzh an-Nasl).